The deepest map : the high-stakes race to chart the world's oceans - Trethewey, Laura (HarperWave, an imprint of HarperCollinsPublishers, 2023)
"The dramatic and action-packed story of the last mysterious place on earth--the world's seafloor--and the deep-sea divers, ocean mappers, marine biologists, entrepreneurs, and adventurers involved in the historic push to chart it, as well as the opportunities, challenges, and perils this exploration holds now and for the future"--